Antibacterial dental resin composites (DRCs) with synthesized bis-quaternary ammonium monomethacrylates as antibacterial agents. (November 2022) - He, Xiaoling; Ye, Linyan; He, Rouye; He, Jingwei; Ouyang, Suidong; Zhang, Jingying
Abstract: Three bi-quaternary ammonium methacrylates (biQAMA-12, biQAMA-14, and biQAMA-16) with different alkyl chain length were synthesized with the purpose of endowing dental resin composites (DRCs) with antibacterial activity without sacrificing physicochemical properties of DRCs. All of biQAMAs were confirmed by 1 H-NMR spectra and incorporated into Bis-GMA/TEGDMA (60 wt/40 wt) resin matrix with a mass fraction of 5 wt% as antibacterial agent. The obtained resin matrixes were mixed with commercial silaned glass fillers at a mass ratio of 30 wt/70 wt to prepare antibacterial DRCs. The double bond conversion (DC), antibacterial activity against S. mutans ., surface charge density, water contact angle, water sorption (WS) and solubility (SL), mechanical properties, and cytotoxicity of biQAMAs containing DRCs were investigated. The DRC without biQAMAs was used as control. The results showed that all biQAMAs containing DRCs had antibacterial rate higher than 90%, and DRC with biQAMA-12 had the highest antibacterial rate due to its highest surface charge density. Adding 5 wt% of biQAMAs would not bring out negative effect on physicochemical properties of DRCs, except for increasing WS, but the resultant WS still met the ISO requirement on WS of restorative materials. Both biQAMA-14 and biQAMA-16 containing DRCs showed higher cytotoxicity than control, thus biQAMA-12 was considered as the optimal antibacterial agent in this research. Highlights: Bi-quaternary ammonium monomers were synthesized as antibacterial agent for DRCs. Bi-quaternary ammonium monomers could endow DRCs with high antibacterial efficiency. Bi-quaternary ammonium monomers would not impair physicochemical properties of DRCs. DRC with Bi-quaternary ammonium monomer biQAMA-12 had low cytotoxicity.